Effect of Intercropping, Row Ratios and Organic Manures on Productivity and Quality of Forage under Semi-arid Regions of Rajasthan - Meena, L R; Mann, J S; Chand, Roop (Annals of Arid Zone, 2016)
A field experiment was conducted at Central Sheep and Wool Research Institute, Avikanagar (Rajasthan), to find out the production performance of perennial Cenchrus setigerus grass with biannual legume Dolichos lablab in different row ratios (1:1, 1:2 and 2:1), in which organic manures were applied alone or in different combinations (control, sheep manure 10 t ha-1), vermicompost (3 t ha-1) and sheep manure and vermicompost (5 t ha-1 and 1.5 t ha-1). The results revealed that green herbage and dry matter production were influenced significantly under different intercropping row ratios. However, green fodder and dry matter increased maximum when D. lablab and Cenchrus were sown in 2:1 row ratio followed by 1:1 and 1:2 row ratios. Similarly, crude protein content was higher in dry matter of D. lablab and Cenchrus planted in 2:1 row ratio (11.60 and 5.36%). The uptake of nitrogen, phosphorus and potassium was maximum in 2:1 row ratio than other row ratios. Overall, there was 15.38% increase in organic carbon and 42.63, 35.34 and 12.72% in available nitrogen, phosphorus and potassium nutrients with 2:1 row ratio as compared to initial soil status. Application of organic manures increased the green herbage and dry fodder yield by 67.83 and 49.79% over control. The crude protein content and nitrogen, phosphorus and potassium uptake also increased significantly with manure application and these were the highest with both organic manures applied together. Soil organic carbon and available nitrogen, phosphorus and potassium were enhanced by 23.07, 44.01, 39.82 and 27.38% with the application of 10 t ha-1 sheep manure as compared to their initial levels in soil. The soil EC was increased and pH decreased with the application of sheep manure (10 t ha-1). Key words: Cenchrus, Dolichos lablab, intercropping, row ratio, sheep manure, vermicompost.